Improving access to care for children with mental disorders: a global perspective. Issue 5 (9th March 2013) - Patel, Vikram; Kieling, Christian; Maulik, Pallab K; Divan, Gauri
Abstract : Developmental disabilities, emotional disorders and disruptive behaviour disorders are the leading mental health-related causes of the global burden of disease in children aged below 10 years. This article aims to address the treatment gap for child mental disorders through synthesising three bodies of evidence: the global evidence base on the treatment of these priority disorders; the barriers to implementation of this knowledge; and the innovative approaches taken to address these barriers and improve access to care. Our focus is on low-resource settings, which are mostly found in low- and middle-income countries (LMIC). Despite the evidence base on the burden of child mental disorders and their long-term consequences, and the recent mental health Gap Action Programme guidelines which testify to the effectiveness of a range of pharmacological and psychosocial interventions for these disorders, the vast majority of children in LMIC do not have access to these interventions. We identify three major barriers for the implementation of efficacious treatments: the lack of evidence on delivery of the treatments, the low levels of detection of child mental disorders and the shortage of skilled child mental health professionals. The evidence based on implementation, although weak, supports the use of screening measures for detection of probable disorders, coupled with a second-stage diagnostic assessment and the use of non-specialist workers in community and school settings for the delivery of psychosocial interventions. The most viable strategy to address the treatment gap is through the empowerment of existing human resources who are most intimately concerned with child care, including parents, through innovative technologies, such as mobile health, with the necessary skills for the detection and treatment of child mental disorders.